'calling‐out' vs. 'calling‐in' prejudice: Confrontation style affects inferred motive and expected outcomes. (7th July 2020) - Woods, Freya A.; Ruscher, Janet B.
Abstract : Laypersons differentiate between two confrontations styles, varying in communication style, perceived motive, and typical context: call‐outs (typically public, non‐accommodating language, and self‐promoting confronter) and call‐ins (typically private, accommodating language, and education‐focused confronter). Popular press espouses a general preference for call‐ins relative to call‐outs, but no empirical work has addressed perceptions of these confrontation styles. To investigate the presumed efficacy of these styles, we modelled communicative differences with Communication Accommodation Theory (CAT), which explores the strategies individuals use to modulate communicative differences with interaction partners. The present studies examined third‐party perceptions of confronter motive and likely outcomes between call‐in and call‐out styles (Study 1) and between typical private and atypical public styles (Study 2) about an anti‐Black comment. We examined responses of participants who imagined themselves taking part in public vs. private call‐in and call‐out confrontations (Study 3). Results showed that these styles are seen as similarly effective in terms of target compliance and internalization, but as operating through different mechanisms. Specifically, call‐in styles facilitated positive inferences of motive, which fostered expectations of positive confrontation outcomes. Additionally, the effects of communication style superseded the impact of context. Results have implications for strategies allies can use to facilitate effective, educational confrontations of prejudice.